Analisis Perubahan Penggunaan Lahan Sawah dari Tahun 2008 – 2018 - Bangun, Yurin; Simanjuntak, Bistok Hasiholan; Sutrisno, Alfred Jansen (UNIVERSITAS NEGERI MAKASSAR, 2021)
Paddy field is a natural resource and have an important role in maintaining the stability of the community's food (rice) production. Banyubiru District is one of the biggest contributors in supplying the rice needs of the people in Semarang Regency. So that the research aims to identify the extent and rate of change in the use of rice fields from 2008 to 2018 in Banyubiru District. The research approach used is based on geographic information systems in analyzing satellite images. The satellite imagery used is multi-resolution imagery such as Landsat 5 TM in 2008, Worldview-2 in 2013, and SPOT 6 in 2018. Image interpretation uses a pixel-based classification method with the maximum likelihood method and on-screen digitization found in ENVI 5.3 and ArcGis software. 10.8. The land use classification system used refers to following the Indonesian National Standard 7654: 201. The results of the study explained that there had been a change in the area of paddy land use in the Banyubiru District from 2008 to 2013 of 68 ha and from 2013 to 2018 of 65 ha. In addition, the rate of land use change from 2008 to 2018 was 14.78 ha / year, so this event can be categorized as a class of rapid land change rate.